Methane turnover and environmental change from Holocene lipid biomarker records in a thermokarst lake in Arctic Alaska. (November 2016) - Elvert, Marcus; Pohlman, John W; Becker, Kevin W; Gaglioti, Benjamin; Hinrichs, Kai-Uwe; Wooller, Matthew J
Arctic lakes and wetlands contribute a substantial amount of methane to the contemporary atmosphere, yet profound knowledge gaps remain regarding the intensity and climatic control of past methane emissions from this source. In this study, we reconstruct methane turnover and environmental conditions, including estimates of mean annual and summer temperature, from a thermokarst lake (Lake Qalluuraq) on the Arctic Coastal Plain of northern Alaska for the Holocene by using source-specific lipid biomarkers preserved in a radiocarbon-dated sediment core. Our results document a more prominent role for methane in the carbon cycle when the lake basin was an emergent fen habitat between ~12, 300 and ~10, 000 cal yr BP, a time period closely coinciding with the Holocene Thermal Maximum (HTM) in North Alaska. Enhanced methane turnover was stimulated by relatively warm temperatures, increased moisture, nutrient supply, and primary productivity. After ~10, 000 cal yr BP, a thermokarst lake with abundant submerged mosses evolved, and through the mid-Holocene temperatures were approximately 3°C cooler. Under these conditions, organic matter decomposition was attenuated, which facilitated the accumulation of submerged mosses within a shallower Lake Qalluuraq. Reduced methane assimilation into biomass during the mid-Holocene suggests that thermokarst lakes are carbon sinks during cold periods. In the late-Holocene from ~2700 cal yr BP to the most recent time, however, temperatures and carbon deposition rose and methane oxidation intensified, indicating that more rapid organic matter decomposition and enhanced methane production could amplify climate feedback via potential methane emissions in the future.